2021
DOI: 10.4322/2176-1523.20212374
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hydrogen blisters during the solution treatment for aluminum alloys

Abstract: The solution treatment of aluminum alloys can be restricted by the presence of porosity defects caused by the moisture present in the process or by the hydrated front on the material surface. Hydrogen blisters cause deleterious effects on mechanical properties and surface finish. However, the formation of bubbles in solid aluminum is not caused only by the known reaction 2Al+3H 2 O=3H 2 +Al 2 O 3 , as it does not explain the interaction of the aluminum oxide layer with the formation mechanisms. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…It was found that the content of the oxygen element in the crater area increased significantly, indicating the high probability of aluminum oxidation in these areas. Therefore, we speculate that when the device is operated or stored in water, the aluminum electrode would react with the water molecules invading the device under the boost of Joule heat, producing hydrogen gas and alumina according to the equation: 2Al + 3H 2 O → 3H 2 + 2Al 3+ + 3O 2– → 3H 2 + Al 2 O 3 . The resulted alumina would reduce the conductivity of the Al electrode due to its insulating nature, consistent with the color change from bright to dark in the SEM image of the Al electrode (Figure b). Furthermore, the continuous formation of hydrogen gas might cause high pressure inside the devices, with the potential for damaging expansion and even destruction of the encapsulating barrier, further accelerating the device failure.…”
Section: Resultssupporting
confidence: 54%
“…It was found that the content of the oxygen element in the crater area increased significantly, indicating the high probability of aluminum oxidation in these areas. Therefore, we speculate that when the device is operated or stored in water, the aluminum electrode would react with the water molecules invading the device under the boost of Joule heat, producing hydrogen gas and alumina according to the equation: 2Al + 3H 2 O → 3H 2 + 2Al 3+ + 3O 2– → 3H 2 + Al 2 O 3 . The resulted alumina would reduce the conductivity of the Al electrode due to its insulating nature, consistent with the color change from bright to dark in the SEM image of the Al electrode (Figure b). Furthermore, the continuous formation of hydrogen gas might cause high pressure inside the devices, with the potential for damaging expansion and even destruction of the encapsulating barrier, further accelerating the device failure.…”
Section: Resultssupporting
confidence: 54%
“…The release of these gases might also partly explain the cracking issues encountered during ECAP-HT. Several examples of «hydrogen blisters» (that is: near-surface cracks due to trapped hydrogen) in conventional Al alloys formed during casting or heat treatments [49][50][51] can be found in the literature.…”
Section: Thermally Induced Damagementioning
confidence: 99%
“…A method commonly used to minimize or eliminate such defects is hot isostatic pressing (HIP). However it has been reported in literature that hydrogen porosity and blistering is a common issue in aluminum castings and L-PBF components [5,6,7]. The hydrogen porosity and blistering present in castings can be managed with appropriate melt strategies.…”
Section: Introductionmentioning
confidence: 99%